The effect of retrieved oocyte count on pregnancy outcomes in an assisted reproduction program - YOLDEMİR, AHMET TEVFİK (SPRINGER HEIDELBERG, 2010)
To determine if women with less than five eggs retrieved do as well as women with more eggs retrieved in terms of pregnancy outcomes in our assisted reproduction program. Two hundred one women undergoing in vitro fertilization treatment at Fertility Unit in Royal Prince Alfred Hospital, University of Sydney, Australia were selected for retrospective evaluation. The women were grouped according to the number of oocytes retrieved at ovum pick-up. Group A consisted of women with less than 5 oocytes, group B with 5 to 10 oocytes and group C with 11 to 15 oocytes collected. Clinical and ongoing pregnancy rates were compared. There was no difference between the groups in terms of clinical and ongoing pregnancy rates. With good IVF lab conditions, if a patient reaches embryo transfer, the number of eggs retrieved should not affect the likelihood of pregnancy outcome in an assisted reproductive technology treatment.
Keywords: Oocyte number; Pregnancy; Fresh embryo transfer; IN-VITRO FERTILIZATION; HUMAN MENOPAUSAL GONADOTROPIN; FOLLICLE-STIMULATING-HORMONE; POOR OVARIAN RESPONSE; INVITRO FERTILIZATION; OVULATION INDUCTION; BASAL; IVF; HYPERSTIMULATION; PRETREATMENT